Evolution of the avian sex chromosomes from an ancestral pair of autosomes - Fridolfsson, Anna-Karin (The National Academy of Sciences, 1998)
Among the mechanisms whereby sex is determined in animals, chromosomal sex determination is found in a wide variety of distant taxa. The widespread but not ubiquitous occurrence, not even within lineages, of chromosomal sex determination suggests that sex chromosomes have evolved independently several times during animal radiation, but firm evidence for this is lacking. The most favored model for this process is gradual differentiation of ancestral pairs of autosomes. As known for mammals, sex chromosomes may have a very ancient origin, and it has even been speculated that the sex chromosomes of mammals and birds would share a common chromosomal ancestry. In this study we showed that the two genes, ATP5A1 and CHD1, so far assigned to the female-specific W chromosome of birds both exist in a very closely related copy on the Z chromosome but are not pseudoautosomal. This indicates a common ancestry of the two sex chromosomes, consistent with the evolution from a pair of autosomes. Comparative mapping demonstrates, however, that ATP5A1 and CHD1 are not sex-linked among eutherian mammals; this is also not the case for the majority of other genes so far assigned to the avian Z chromosome. Our results suggest that the evolution of sex chromosomes has occurred independently in mammals and birds.